Development of [89Zr]Zr-DFO-hu3F8 and [225Ac]Ac-DOTA-hu3F8 Theranostic Pairs Targeting GD2 in Neuroblastomas - Lingling Zheng (1628176) (2025)
Relapsed and refractory high-risk neuroblastoma (NBL) patients have limited treatment options and a poor prognosis, highlighting the urgent need for novel targeted therapies. This study evaluates the GD2-targeting PET imaging agent [89Zr]Zr-DFO-hu3F8 and the radioimmunotherapy agent [225Ac]Ac-DOTA-hu3F8 in NBL animal models. The GD2 overexpressing IMR32 tumor was assessed by using [89Zr]Zr-DFO-hu3F8 PET imaging to confirm targeting efficacy. The safety and therapeutic efficacy of [225Ac]Ac-DOTA-hu3F8 were evaluated in GD2-positive NBL xenografts. ImmunoPET revealed the high and sustained uptake of [89Zr]Zr-DFO-hu3F8 in IMR32 tumors compared to the [89Zr]Zr-DFO-IgG control group. In vitro biodistribution analysis showed that a tumor uptake was 58.47 ± 3.64%ID/g at 168 h post-injection. A single dose of [225Ac]Ac-DOTA-hu3F8 treatment significantly suppressed tumor growth, with most tumors (4/5) achieving complete remission at medium and high doses (11.1 and 18.5 kBq). Overall, our findings demonstrate that alpha-targeted therapy based on hu3F8 holds significant potential as a promising curative treatment strategy for NBL.